Direction of Trade Statistics Yearbook, 2002. (Direction of Trade Statistics; 2002, 2002)
The Direction of Trade Statistics yearbook, usually published in September, contains data on the value of merchandise exports and imports between each country and all its trading partners. The Yearbook provides seven years of data for 183 countries and two sets of world and area summaries: world and area trade as seen by the reporting countries, and as seen by the partner countries to those transactions.